School Accountability, Postsecondary Attainment, and Earnings - Deming, David J.; Cohodes, Sarah; Jennings, Jennifer; Jencks, Christopher (The Review of Economics and Statistics, 2016)
We study the impact of accountability pressure in Texas public high schools in the 1990s on postsecondary attainment and earnings, using administrative data from the Texas Schools Project. Schools respond to the risk of being rated Low Performing by increasing student achievement on high-stakes exams. Years later, these students are more likely to have attended college and completed a four-year degree, and they have higher earnings at age 25. However, we find no overall impact of accountability pressure to achieve a higher rating, and large negative impacts on attainment and earnings for the lowest-scoring students.